Influenza H5N1 and H1N1 Virus Replication and Innate Immune Responses in Bronchial Epithelial Cells Are Influenced by the State of Differentiation - Chan, Renee W. Y.; Yuen, Kit M.; Yu, Wendy C. L.; Ho, Carol C. C.; Nicholls, John M.; Peiris, J. S. Malik; Chan, Michael C. W. (PloS one, 2010)
Influenza H5N1 virus continues to be enzootic in poultry and transmits zoonotically to humans. Although a swine-origin H1N1 virus has emerged to become pandemic, its virulence for humans remains modest in comparison to that seen in zoonotic H5N1 disease. As human respiratory epithelium is the primary target cells for influenza viruses, elucidating the viral tropism and host innate immune responses of influenza H5N1 virus in human bronchial epithelium may help to understand the pathogenesis. Here we established primary culture of undifferentiated and well differentiated normal human bronchial epithelial (NHBE) cells and infected with highly pathogenic influenza H5N1 virus (A/Vietnam/3046/2004) and a seasonal influenza H1N1 virus (A/Hong Kong/54/1998), the viral replication kinetics and cytokine and chemokine responses were compared by qPCR and ELISA. We found that the in vitro culture of the well differentiated NHBE cells acquired the physiological properties of normal human bronchi tissue which express high level of alpha2-6-linked sialic acid receptors and human airway trypsin-like (HAT) protease, in contrast to the low expression in the non-differentiated NHBE cells. When compared to H1N1 virus, the H5N1 virus replicated more efficiently and induced a stronger type I interferon response in the undifferentiated NHBE cells. In contrast, in well differentiated cultures, H5N1 virus replication was less efficient and elicited a lower interferon-beta response in comparison with H1N1 virus. Our data suggest that the differentiation of bronchial epithelial cells has a major influence in cells' permissiveness to human H1N1 and avian H5N1 viruses and the host innate immune responses. The reduced virus replication efficiency partially accounts for the lower interferon-beta responses in influenza H5N1 virus infected well differentiated NHBE cells. Since influenza infection in the bronchial epithelium will lead to tissue damage and associate with the epithelium regeneration, the data generated from the undifferentiated NHBE cultures may also be relevant to disease pathogenesis.